Renewable energy community and the European energy market: main motivations. Issue 7 (July 2020) - Soeiro, Susana; Ferreira Dias, Marta
Abstract: With the implementation of the EU's key climate and energy policy objectives, there is a transition to a new energy system where renewable energy sources are pushed and where new technologies need to be developed and adopted. The energy transition may result in deeper participation of individual consumers or citizens in community-based initiatives. Those communities operate collectively in the energy market producing RE or in local networks, based on local collaborations. The development of energy communities is not the same in all member state. Moreover, it is noted that their development is different depending on the European country. The aim of this paper is to collect data, using a survey, to study and to better understand what the citizen energy initiatives are, their main features and the motivations of individuals to participate on it. The citizens participation is a crucial point for the development of this type of communities. The main motivation for participation in these communities seems to be concerns about environmental and climate impacts. We also note that in these communities the trust is very important for the development of any RE project. Abstract : Energy; Economics; Renewable energy; Motivations; Energy legislation; European Union; Citizen energy communities; Environmental economics; Behavioral economics; Microeconomics; Econometrics; Energy economics.